Advanced Nonlinear Studies (De Gruyter, 2001)
Advanced Nonlinear Studies (ANS) is aimed at publishing scholarly articles on nonlinear problems, particularly those involving Differential and Integral Equations, Dynamical Systems, Calculus of Variations, and related areas. It will also publish novel and interesting applications of these areas to problems in biology, engineering, materials sciences, physics and other sciences.